A Coulometric Study of the Corrosion Kinetics of Carbon Steel in Microgram Range - Kuzmak, A.E.; Kozheurov, A.V. (Innovations in Corrosion and Materials Science (Discontinued), 2017)
Background: Results of a study on the initial stage of corrosion damage of carbon steel in 0.5mol/l NaCl by high-precision Coulometric Registration of Corrosion Products (CRCP) of the metal surface and in the corrosive medium are reported. Methods: During the measurements, the method of coulometric determination of corrosion products developed by the authors was used. Result: An accurate quantitative determination of “initiation phase of corrosion” allowed to find a correlation between the early stage of the process and its subsequent development of corrosion.
Keywords: coulometry